Penyelesaian Sengketa Perdata Dalam Pembentukan Perusahaan Oleh Investor Asing Pemegang Golden Visa - Tarigan, Stevani A; Simammora, Janpatar (Faculty of Law, Diponegoro University, 2024)
Law No. 22 of 2023 on Visa and Residence Permit categorizes Limited Stay Visa, Limited Stay Permit, Permanent Stay Permit, and Re-entry Permit in different categories. Foreign investors holding a Golden Visa can form a company, invest, repatriate, merge families, or build a second home but still follow Indonesian government regulations such as minimum investment capital. Golden Visa holders have legal protection rights and special investment facilities. The problem that the author examines is disputes arising from the process of company formation by Golden Visa holders, knowing the civil dispute resolution mechanism for Golden Visa holders. The method used in this research is a qualitative approach that has a descriptive nature. This type of research is normative legal research with a focus on norms and applicable legal regulations. The research approach is normative legal and case study, analyzing previously existing cases or relevant cases. The data needed are legislation, court decisions and secondary legal materials such as journals, literature and related articles from clear sources. The results of this study indicate that the resolution of disputes faced by foreign investors holding Golden Visas, such as default, unilateral cancellation of contracts, or profit sharing that is not in accordance with the agreement can be resolved through alternative non-litigation resolution, namely international arbitration. In the arbitration process, the disputing parties will receive legal protection, because laws and regulations must protect the rights to assets, property, and fast access to the visa processing process. The recommendation is that arbitration be used to resolve disputes over the formation of companies holding Golden Visas, and if the Golden Visa grants exclusive rights to investors, then the Indonesian government must consider special regulations on the Golden Visa.